Cherubism: Report of a Case - Ram, Sachin G.; Ajila, Vidya; Babu, Subhas G.; Shetty, Pushparaja; Hegde, Shruthi; Pillai, Devika S. (Journal of Health and Allied Sciences NU, 2020)
Cherubism, also known as familial fibrous dysplasia of the jaws or familial multilocular cystic disease is a rare hereditary, developmental disorder. This condition affects the posterior region of the jaws bilaterally in children belonging to the age group of 2 to 5 years. Maximum growth is recorded till puberty after which the lesion regresses over a period of time. Cherubism classically manifests radiographically as bilateral, multilocular radiolucencies affecting the posterior mandible and maxilla. Therapeutic management varies from patient to patient and is directed mainly by esthetic and functional concerns. The present report highlights the clinical and radiographic features of nonfamilial cherubism in a 6-year-old girl.
Keywords: cherubism; multilocular; mandible